2015
DOI: 10.1007/s00384-015-2260-4
|View full text |Cite
|
Sign up to set email alerts
|

Circular anastomotic experimental fibrin sealant protection in deep colorectal anastomosis in pigs in a randomized 9-day survival study

Abstract: Circular anastomotic protection with the experimental fibrin sealant blocked anastomotic full wall defects, preventing peritonitis and significantly reducing the AL rate from 25 to 5 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
(59 reference statements)
2
10
1
Order By: Relevance
“…In our previous follow-up survival study, we observed a 20% AL rate in CDSA after LAR until the ninth postoperative day compared with 5% leakage rate in the therapy group with an additional circular extraluminal fibrin glue sealant. 13 In our present 21-day follow-up trial, there were 20% ALs in the control group compared with 0% in the sealant group. The observed rate of leakages is within the range of literature in human patients.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…In our previous follow-up survival study, we observed a 20% AL rate in CDSA after LAR until the ninth postoperative day compared with 5% leakage rate in the therapy group with an additional circular extraluminal fibrin glue sealant. 13 In our present 21-day follow-up trial, there were 20% ALs in the control group compared with 0% in the sealant group. The observed rate of leakages is within the range of literature in human patients.…”
Section: Discussionmentioning
confidence: 49%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Thus, our experimental model in pig again proved to be similar to the human pathomechanism of AL after LAR. 12,13 Moreover, we observed intraluminal wall defects at the crossing of linear and circular stapler in both trials. While these wall defects led to AL in the control group, the fibrin glue sealant prevented leakages as well after 9 postoperative days in the previous trial.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A lot of studies have been carried out to find materials and surgical techniques for the purpose of protecting high-risk gastrointestinal anastomosis [5][6][7] . Peritoneum, collagen, and synthetic materials (polymers) and sealants have been investigated in previous studies for the purpose of protecting anastomosis and preventing AL [5][6][7][8][9] . Most of these studies are animal studies, and satisfactory results have not been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic (peritoneum), xenolog (collagen), and synthetic materials (polymers) and sealants (fibrin) have been previously tested to protect the anastomosis and prevent AL and adherence formation. [6][7][8][9][10] Most of the trials were animal trials and have not yet been able to identify the optimal barrier to prevent adhesions in a sustainable way. 11 In most trials, detailed information on materials and methods according to IDEAL criteria is missing.…”
Section: Introductionmentioning
confidence: 99%